VIRTUALITY ON CURRENT FORMATIVE PROCESSES (Revista Electrónica Calidad en la Educación Superior, 2016)
The training processes should characterize is by the update constant that can respond to the needs of them contexts in which is developed. It is as well as technology has burst so that thinking about virtual education is less and less likely, its applications extend not only to the traditional educational contexts (school, College and University), but to those contexts labour. These new models of learning are many advantages including saving resources, possibility to carry out education and training to the distance among others, while we face serious questions about what we understand by training processes and their actors, as the role of teacher-student. Is undeniable that the technology will be each time more embedded in them processes training virtual, by what these questions and assessments must rethink is and discuss is.